THE EFFECT OF LOCATION, PRICE, AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS AT d’BestO IN SUNGAI PENUH CITY - Wahyuni, Endah Sri; Bustami, Alek Wissalam; Sumanti, Eva; Putra, Eka; Harahap, Samsul Bahry; Bustami, Bustami (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
This study aims to determine the effect of Location, Price and Product Quality on d’BestO Purchasing Decisions in Sungai Penuh City. The population in this study were d’BestO consumers in Sungai Penuh City. The sample in the study was taken using a non probability technique using the accidental sampling method. Data analysis in this study used the SPSS 26 program. The results of the analysis and discussion showed that the location variable did not have a significant effect on purchasing decisions, price had a significant effect on purchasing decisions and the product quality variable did not have a significant effect on purchasing decisions and location, price and product quality had a significant effect on purchasing decisions at d'BestO in Sungai Penuh City.